The Effect of Using Film Media on PKn Learning Outcomes (Class III Subjects at SD Negeri Sepathi Pituruh Districat, Purworejo Regency) - Heni Kusrini; Septiyati Purwandari (Prosiding University Research Colloquium, 2022)
This study aims to determine the effect of using film media on the learning outcomes of class III PKN SD Negeri Sepati, Pituruh District, Purworejo Regency. The type of research used is a quantitative pre-Experimental Sign One Group Pretest-Posttest research with third grade students at SD Negeri Sepathi Pituruh with a total of 13 students consisting of 8 boys and 5 girls selected by saturated sampling. Data collection techniques in the form of tests (Pretest and Posttest). The analysis used is the Wilcoxon test by comparing the Pretest and Posttest scores. This analysis is used to determine the effect of using film media on PKN learning outcomes. This is done by looking at the average value of the Pretest and Posttest before and before being treated using film media. The average pretest score. which is 53, while the Posttest average value is 78.4. The increase in PKN learning outcomes can be seen from the use of the Wilcoxon test which shows that the significance value (2-tailed) is 0.001 <0.05. This indicates a change in the concept of significance after treatment, so it can be said that the use of film media affects the learning outcomes of class III Civics. Sepathi Elementary School, Pituruh District, Purworejo Regency.